2018
DOI: 10.1111/jph.12718
|View full text |Cite
|
Sign up to set email alerts
|

Colonization ability as an indicator of enhanced biocontrol capacity—An example using two Bacillus amyloliquefaciens strains and Botrytis cinerea infection of tomatoes

Abstract: An understanding of biocontrol activities is important when developing microorganism‐based alternatives to conventional fungicides. From our bacterial collection, we selected two strains (BBC023 and BBC047) for their outstanding antagonistic capacity against fungal phytopathogens and growth‐promoting abilities towards Arabidopsis thaliana. According to physiological and molecular characterizations, both strains were classified as Bacillus amyloliquefaciens and were tested against Botrytis cinerea in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…Growth promotion capacity has, in some cases, been linked to the mode of application used. Salvatierra-Martínez et al (2018) [ 13 ] demonstrated that only radicular applications of B. subtilis strains BBC023 and BBC047 are capable of enhancing biomass production. Similarly, Esitken et al (2010) [ 63 ] found that not all PGPR strains of the genus Bacillus act in a similar fashion in strawberry plants and that crop yields, in some cases, increase following root applications of Bacillus strain M3 and, in other cases, after foliar applications of Bacillus OSU142.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth promotion capacity has, in some cases, been linked to the mode of application used. Salvatierra-Martínez et al (2018) [ 13 ] demonstrated that only radicular applications of B. subtilis strains BBC023 and BBC047 are capable of enhancing biomass production. Similarly, Esitken et al (2010) [ 63 ] found that not all PGPR strains of the genus Bacillus act in a similar fashion in strawberry plants and that crop yields, in some cases, increase following root applications of Bacillus strain M3 and, in other cases, after foliar applications of Bacillus OSU142.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Spanish Ministry of Agriculture, Fisheries and Food (MAPA), in the 2017/2018 period, Spain was one of the largest producers of strawberries in Europe (26%), with exports of 461.3 million euros, and of tomatoes in the world, with 4.7 million hectares devoted to this crop. In 2016, world tomato production reached 177 million tons according to the Food and Agriculture Organization of the United Nations Statistics Division (FAOAST), with Spain accounting for around 812,571 tons (MAPA) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus amyloliquefaciens BBC047 strain was provided by CEAZA (Centro de Estudios Avanzados en Zonas Áridas, La Serena, Chile). Recently, Salvatierra‐Martínez et al characterized its capacity to promote plant growth and to control grey mold disease ( Botrytis cinerea ) in tomato. For inoculation, the strain was cultivated in LB media for 36 h (30 °C, 150 rpm) until the beginning of the stationary phase (10 9 CFU mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…B. amyloliquefaciens strains have been proven to be successful biocontrol agents in the field for a wide range of pathogens, such as Sclerotinia sclerotiorum causing canola stem rot ( Fernando et al, 2007 ), and fusarium head blight on durum wheat ( Schisler et al, 2002 ). Salvatierra-Martinez et al (2018) described biocontrol activity of two B. amyloliquefaciens strains against B. cinerea on tomato plants. These two trains had similar antagonistic effect in vitro , while strain BBC047 showed better results in planta .…”
Section: Direct Interactionsmentioning
confidence: 99%
“…Adaptation factors are often overlooked in biocontrol research. However, low efficacy of biocontrol agents in field studies is often due to a lack of adaptation rather than a lack of biocontrol factors (Zeriouh et al, 2014;Salvatierra-Martinez et al, 2018). Moreover, a successful biocontrol agent needs a variety of adaptation and biocontrol factors to inhibit a pathogen and improve plant health (Köhl et al, 2019).…”
Section: Introductionmentioning
confidence: 99%